Tunable coupled terahertz surface plasmon polaritons in graphene metamaterials. (27th March 2019) - Tao, Z H; Dong, H M; Duan, Y F; Liu, J L; Cao, B H
Abstract: We propose a metamaterial structure based on graphene-dielectric systems. Double tunable coupled terahertz (THz) surface plasmon polaritons (SPPs) are realized in such graphene metamaterials. The coupled SPPs exhibit extraordinary and interesting properties, which are very different from the conventional SPPs reported in recent years. The coupled SPPs split into an optic mode and an acoustic mode. Importantly, the optic SPP strong coupling with light fields can be effectively excited without specific coupling devices in the proposed metamaterial. Moreover, the optic SPP can be conveniently tuned by a gate voltage. More interestingly, the electrically-regulated THz SPPs are tunably achieved. Our theoretical study highlights the applications of graphene metamaterials as tunable THz plasmonic devices and advanced nanophotonic devices.